A literature review of golden eagle populations and reproductive response to diet in the Uintah Basin - Carlson, Craig M. (University of Wisconsin--Stout, 2018)
The golden eagle (Aquila chrysaetos) is a large raptor with resident and migrant populations in many western states. It is a monogamous species that will typically only initiate a clutch once per year. Habitat, prey species population, and dietary breadth influence reproductive success of the eagle. Here, an examination of the cold desert habitat, specifically the Uintah Basin, Utah and the surrounding mountains of the Western Cordillera were considered. Populations of prey population decline explained by a bottom-up trophic scale species may determine fecundity rates in some populations, with resulting decline correlating to prey species abundance. This association of specific prey population decline and eagle reproductive rate decline was not witnessed in all studies reviewed. Volume of prey drives reproductive success beyond impacts of dietary breadth, which is beneficial during prey population down-cycles. This is especially true for paired eagles with direct correlation between reproductive success and prey abundance. High nest fidelity, regardless of prey population, encourages nesting pairs to return to established nests but impairs the eagles due to climate change, specifically increased temperatures that affect nesting success. Suggestions are provided for future research to ensure survival of these populations.
Keywords: Golden eagle; Predation (Biology); Uinta Basin (Utah and Colo.)